Combined outer volume suppression and T2 preparation sequence for coronary angiography. Issue 6 (17th December 2014) - Luo, Jieying; Addy, Nii Okai; Ingle, R. Reeve; Hargreaves, Brian A.; Hu, Bob S.; Nishimura, Dwight G.; Shin, Taehoon
Abstract : Purpose: To develop a magnetization preparation sequence for simultaneous outer volume suppression (OVS) and T 2 weighting in whole‐heart coronary magnetic resonance angiography. Methods: A combined OVS and T 2 preparation sequence (OVS‐ T 2 Prep) was designed with a nonselective adiabatic 90° tipdown pulse, two adiabatic 180° refocusing pulses, and a 2D spiral −90° tipup pulse. The OVS‐ T 2 Prep preserves the magnetization inside an elliptic cylinder with T 2 weighting, while saturating the magnetization outside the cylinder. Its performance was tested on phantoms and on 13 normal subjects with coronary magnetic resonance angiography using 3D cones trajectories. Results: Phantom studies showed expected T 2 ‐dependent signal amplitude in the spatial passband and suppressed signal in the spatial stopband. In vivo studies with full‐field‐of‐view cones yielded a passband‐to‐stopband signal ratio of 3.18 ± 0.77 and blood‐myocardium contrast‐to‐noise ratio enhancement by a factor of 1.43 ± 0.20 ( P < 0.001). In vivo studies with reduced‐field‐of‐view cones showed that OVS‐ T 2 Prep well suppressed the aliasing artifacts, as supported by significantly reduced signal in the regions with no tissues compared to the images acquired without preparation ( P < 0.0001). Conclusion: OVS‐ T 2 Prep is a compact sequence that can accelerate coronary magnetic resonance angiography by suppressing signals from tissues surrounding the heart while simultaneously enhancing the blood‐myocardium contrast. Magn Reson Med 74:1632–1639, 2015. © 2014 Wiley Periodicals, Inc.